Harmonization and equivalence in milk and dairy products standards - moving towards regional trade blocks: Case study from East Africa - Kurwijila, Lusato R.; Mosha, C.J.S.; Omore, Amos O.; Lore, Tezira A. (2008)
The dairy industry contributes about 3, 5, and 7% of the GDP of Kenya, Tanzania and Uganda respectively. Milk production is estimated to be about 5 million tons per annum, 60% of which is produced in Kenya. More than 80% of the milk is traded informally as raw milk. The processing industry works at less than 30% of the installed capacity of about 2.8 million litres per day. Except for Kenya, demand for milk and dairy products exceeds domestic production even in years of normal rainfall and the deficit is growing. The gap between supply and demand is filed by intraregional and extra-regional imports which together amounted to 31,555 metric tons in 2003 worth 8.3 million US $. Intra-regional trade in dairy products is constrained by inadequate milk processing and marketing infrastructure, seasonality of supplies, tariff and non-tariff barriers as well as sanitary and quality standards issues. The paper highlights on the efforts that have been taken by the East African Community (EAC) towards harmonization of standards for milk and dairy products. In view of the predominance of the informal milk trade, dairy regulatory authorities also see training and certification of informal milk trade as a starting point towards quality improvement in the entire dairy value chain and establishment of equivalence in competencies of all key role players through standardized training curricular. A programme for training and certification of informal milk traders initiated by the Association for Agricultural Research in East and Central Africa (ASARECA) is presented and discussed in that context. Establishment of equivalent or uniform standards and improvements in hygienic handling of milk through enhanced competences of all key dairy value chain role players within the EAC is expected to contribute towards enhancing cross-border trade in milk and dairy products.